Pentingnya Disiplin Kerja Pada Perusahaan - Samsudin, Acep; Hermansyah, Krisna Putra; N.Z, Muhammad Ryan; Mahara, Cendana Izha (Peneliti.net, 2024)
This research highlights the importance of work discipline in the context of businesses and organizations. Through a literature review analysis, it elucidates the role of work discipline in influencing employee productivity, operational efficiency, company culture, and product or service quality. The findings indicate that good work discipline helps reduce workplace conflicts, enhances job satisfaction, and saves the company time and resources. Thus, this research concludes that work discipline is a critical factor in achieving success and sustainable growth in the business world